(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to study decision making using producing factors under the concept of green economy to enhance the community’s economic sustainability for 250 agricultural households who grow glutinous rice, animal feed maize and potato in an area of 2,500 Rai in Mae-Faek Mai Sub-District, Sansai District, Chiang Mai Province. The study employs the Fuzzy Analysis Hierarchical Process (FAHP) together with Multi-goal and Multi-Period Linear Programming. The results reveal that growing in-season glutinous rice alternating with potato is the most appropriate way to increase net revenue and to decrease the amount of greenhouse emission, followed by growing in-season glutinous rice alternating with animal feed maize as this helps income stability when drought occurs. In contrast, growing in-season glutinous rice alternating with off-season glutinous rice is not only affected by a lack of water resources, but also increases the amount of greenhouse gas from the growing process.